Sodium-ion battery pole piece containing composite nano silicon carbide and preparation method of sodium-ion battery pole piece
By adding nano silicon carbide particles and silicon carbide whiskers to the sodium ion battery electrode sheet to form a composite thermal conductivity network, the problem of heat accumulation during the charging and discharging of sodium ion batteries is solved, and the thermal conductivity and cycling stability of the battery are significantly improved.
Patent Information
- Application Number
- CN202510023074.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-07
AI Technical Summary
Sodium ion batteries generate a large amount of heat during charging and discharging, causing the battery temperature to rise rapidly, which in turn causes aging, capacity drop and safety hazards.
By adding 0.5Wt% to 5Wt% nano silicon carbide particles and 0.5Wt% to 5Wt% silicon carbide whiskers to the sodium ion battery electrode sheet, a composite thermal conductivity network is formed to enhance the thermal conductivity of the battery electrode sheet.
It significantly improves the thermal conductivity of the sodium ion battery pole, improves the thermal management of the battery, reduces the temperature rise of the battery, improves the cycle stability and safety, and maintains good electrochemical performance.
Smart Images

Figure CN119833574A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of sodium ion battery pole pieces, in particular to a sodium ion battery pole piece containing composite nano silicon carbide and a preparation method thereof. Background Art
[0002] As a potential alternative to lithium-ion batteries, sodium-ion batteries have attracted much attention due to their abundant resources and low cost. However, sodium-ion batteries still face challenges in terms of energy density, cycle stability, and thermal management. Sodium-ion batteries generate a lot of heat during the charging and discharging process. If this heat cannot be dissipated in time, the battery temperature will rise rapidly. Sodium-ion batteries will cause many problems at high temperatures. For example, high temperature will accelerate the aging of the chemical substances inside the battery and shorten the battery life; under high temperature conditions, the effective capacity of the battery will drop significantly, resulting in a reduction in the use time of the device when fully charged; because the chemical properties of its electrolyte and electrode are more unstable at high temperatures, high temperature environments can cause gas to be generated inside the battery, which in turn causes the battery to swell and even cause explosions or combustion. How to avoid battery overheating and improve battery performance has become an urgent problem to be solved in this field. Summary of the invention
[0003] The purpose of the present invention is to overcome the shortcomings of the prior art that a large amount of heat is generated during charging and discharging, and the sodium ion pole piece will age rapidly at high temperatures. A sodium ion battery pole piece containing composite nano-silicon carbide and a preparation method thereof are provided. The thermal conductivity is enhanced by adding silicon carbide, thereby enhancing the thermal conductivity of the sodium ion battery pole piece and preventing the sodium ion battery from aging at high temperatures.
[0004] The purpose of the present invention is mainly achieved through the following technical solutions: A sodium ion battery pole piece containing composite nano silicon carbide, a sodium ion battery pole piece containing composite nano silicon carbide, characterized in that the sodium ion battery pole piece includes the following proportions: 0.5Wt%~5Wt% nano silicon carbide particles; 0.5Wt%~5Wt% Silicon carbide whiskers; Wherein, the weight ratio of the nano silicon carbide particles to the silicon carbide whiskers is 1-2:1.
[0005] At present, in the existing technology, research and development usually focuses on the material activity of the current collector to obtain a smaller resistivity, or from the perspective of material structure, the battery electrode can carry more active substances. This can effectively improve the performance of the battery, thereby achieving a breakthrough in the battery energy density. However, on this basis, the application stability of the sodium-ion battery is squeezed out, so that the sodium-ion battery cannot effectively dissipate heat during the charging and discharging process, resulting in high temperature of the sodium-ion battery. When the sodium-ion battery has a continuous high temperature, it will cause rapid aging of the sodium-ion battery, thereby affecting the service life of the sodium-ion battery.
[0006] The weight ratio of the nano silicon carbide particles to the silicon carbide whiskers is 1-2:1, which can better form a point-line composite heat-conducting network, thereby enhancing the thermal conductivity of the battery pole piece of the present invention.
[0007] The present invention considers adding a thermal conductor to the battery pole piece to enhance the thermal conductivity of the battery pole piece, thereby enhancing the heat dissipation efficiency of the sodium ion battery. There are many forms and types of thermal conductors. The materials with excellent thermal conductivity are diamond (2300W / m·K), diamond (>1000W / m·K), silicon carbide (490W / m·K), silver (429W / m·K), pure copper (401W / m·K), gold (317W / m·K), pure aluminum (237W / m·K), and brass (70~183W / m·K). Diamond has excellent thermal conductivity, but electrical insulation. Silver, copper, and gold are relatively expensive; therefore, silicon carbide is an ideal thermal conductive material. In addition to material properties, the microstructural characteristics and distribution of the thermal conductor are important factors affecting thermal conductivity. Granular thermal conductive materials are zero-dimensional structures, while fiber thermal conductive materials are one-dimensional structures. The thermal conductor with a fine granular zero-dimensional structure is a point contact, and the thermal conductor with a linear one-dimensional structure is a line contact. The granular thermal conductor is more easily evenly dispersed on the surface of the active material particles, in close contact with the active material, to form a good short-range thermal path, but it is not conducive to forming a long-range thermal path in the thickness direction of the entire electrode. The present invention sets the material of 0.5~5Wt% of nano silicon carbide particles and 0.5~5Wt% of silicon carbide whiskers, adds two different forms of silicon carbide thermal conductors to the battery pole piece, utilizes the advantages of each different form of silicon carbide thermal conductor, and adopts a mixed thermal conductor of two structures to form a complete thermal conductive network. By adding nano silicon carbide particles and silicon carbide whiskers, the sodium ion battery pole piece of the present invention significantly improves the thermal conductivity, helps to improve the thermal management of the battery, reduces the temperature rise of the battery, and improves the cycle stability and safety of the battery. At the same time, the optimized component ratio and preparation process ensure that the pole piece has good electrochemical properties, providing strong technical support for the application of sodium ion batteries.
[0008] Furthermore, the particle size of the nano silicon carbide particles is 50 nm to 500 nm, the diameter of the silicon carbide whiskers is 0.2 um to 0.5 um, and the length of the silicon carbide whiskers is 2 um to 10 um.
[0009] The particle size of the nano silicon carbide particles is 50 nm to 500 nm, which can ensure uniform coating of the active substance and prevent the particles from being too small to be dispersed; The diameter of the silicon carbide whisker is 0.2 um to 0.5 um, and the length of the silicon carbide whisker is 2 um to 10 um, which can match the particle size of the active material particles. On the basis of ensuring uniform connection of different active material particles, it can also prevent the risk of too long particle size and difficulty in coating.
[0010] Furthermore, the following proportions are included: 0.5wt%~5wt% conductive agent; 1wt%~5wt% adhesive; 97.5wt%~80wt% active matter.
[0011] The active material in the present invention is an active material for sodium ion batteries, such as layered oxides, polyanion types, and lithium battery active materials can also be used. Specifically, the active material can be an active material in the crystal phase of Na2Ti6O13, a melt solidified body represented by NaxMyP2O7, Na4Ni3(PO4)2(P2O7) crystals, NaNiPO4 crystals, silicon inclusion compound electrode active materials and the like.
[0012] A method for preparing a sodium ion battery pole piece containing composite nano-silicon carbide comprises the following steps: S1: Add 1-5 parts by weight of adhesive to 100 parts by weight of solvent and stir evenly to obtain adhesive solution; S2: adding 0.5-5.5 parts by weight of nano silicon carbide particles and 0.5-5.5 parts by weight of silicon carbide whiskers to the adhesive glue, wherein the nano silicon carbide particles and the silicon carbide whiskers are added to the adhesive glue in a weight ratio of 1-2:1 and dispersed evenly to form a thermal conductive glue; S3: adding 0.5-6 parts by weight of a conductive agent into 100 parts of a thermally conductive adhesive liquid and dispersing the conductive agent evenly to form a conductive and thermally conductive slurry; S4: adding 60-200 parts by weight of the active material into 100 parts of the conductive and thermal conductive slurry, and dispersing and homogenizing to obtain an electrode slurry; The electrode slurry is coated on the surface of the current collector with a coating thickness of 100 um to 300 um to obtain a battery electrode containing composite nano-silicon carbide.
[0013] Furthermore, the particle size of the active material is 5-10 um.
[0014] The particle size of the active material in the present invention is 5-10 um, thereby ensuring sufficient material stability and better electrical properties.
[0015] Furthermore, the coating thickness of the battery pole piece containing composite nano-silicon carbide is 100~300um.
[0016] The coating thickness is guaranteed to be within the range of 100 um ~300 um, which can ensure that the electrode has good electrical properties.
[0017] Furthermore, the solid content of the electrode slurry is 40 wt% to 65 wt%, and the viscosity of the electrode slurry is 3000 mPa·s to 5000 mPa·s.
[0018] In summary, the present invention has the following beneficial effects compared with the prior art: By adding nano silicon carbide particles and silicon carbide whiskers, the sodium ion battery pole piece of the present invention significantly improves thermal conductivity, helps improve battery thermal management, reduces battery temperature rise, and improves battery cycle stability and safety. At the same time, the optimized component ratio and preparation process ensure that the pole piece has good electrochemical properties, providing strong technical support for the application of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings: Figure 1 This is a SEM image of a sodium ion battery electrode prepared in Example 1 of the present invention; Figure 2 This is a schematic diagram of the thermal conductive network structure of the sodium ion battery electrode prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0020] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments and drawings. The exemplary embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0021] Example 1: S1: Add 2.0 g of adhesive into 100 g of solvent and stir until completely dissolved to obtain adhesive glue; S2: Add 2.0 g of nano silicon carbide particles and 1.0 g of silicon carbide whiskers to 102 g of adhesive glue in proportion, stir and disperse at high speed for 30 minutes to form a thermal conductive glue; S3: Add 2.0 g of conductive agent into 105 g of thermal conductive adhesive and continue to disperse for 30 minutes to form a conductive thermal conductive slurry; S4: Add 93g of active material to 10g of conductive and thermally conductive slurry, stir and disperse at high speed for 60 minutes, adjust the viscosity to 3000-5000mPa·s to obtain electrode slurry. Coat the electrode slurry on the surface of the current collector, control the coating thickness to 150um, dry and roll to obtain a battery pole piece containing composite nano-silicon carbide.
[0022] Example 2: S1: Add 2.0 g of adhesive into 100 g of solvent and stir until completely dissolved to obtain adhesive glue; S2: Add 1.0 g of nano silicon carbide particles and 0.5 g of silicon carbide whiskers to 102 g of adhesive glue in proportion, stir and disperse at high speed for 30 minutes to form a thermal conductive glue; S3: Add 2.0 g of conductive agent to 103.5 g of thermal conductive adhesive and continue to disperse for 30 minutes to form a conductive thermal conductive slurry; S4: Add 94.5g of active material to 105.5g of conductive and thermally conductive slurry, stir and disperse for 60 minutes, adjust the viscosity to 3000-5000mPa·s to obtain electrode slurry. Coat the electrode slurry on the surface of the current collector, control the coating thickness to 150um, dry and roll to obtain a battery pole piece containing composite nano-silicon carbide.
[0023] Example 3: S1: Add 2.0 g of adhesive into 100 g of solvent and stir until completely dissolved to obtain adhesive glue; S2: Add 1.0 g of nano silicon carbide particles and 1.0 g of silicon carbide whiskers into 102 g of adhesive glue in proportion, and stir and disperse at high speed for 30 minutes to form a thermal conductive glue; S3: Add 2.0 g of conductive agent into 104 g of thermal conductive adhesive and continue to disperse for 30 minutes to form a conductive and thermal conductive slurry; S4: Add 94.0g of active material to 106g of conductive and thermally conductive slurry, stir and disperse for 60 minutes, adjust the viscosity to 3000-5000mPa·s to obtain electrode slurry. Coat the electrode slurry on the surface of the current collector, control the coating thickness to 150um, dry and roll to obtain a battery pole piece containing composite nano-silicon carbide.
[0024] Embodiment 4: S1: Add 2.0 g of adhesive into 100 g of solvent and stir until completely dissolved to obtain adhesive glue; S2: Add 0.5 g of nano silicon carbide particles and 0.5 g of silicon carbide whiskers into 102 g of adhesive glue in proportion, stir and disperse at high speed for 30 minutes to form a thermal conductive glue; S3: Add 2.0 g of conductive agent into 103 g of thermal conductive adhesive and continue to disperse for 30 minutes to form a conductive thermal conductive slurry; S4: Add 95.0g of active material to 105g of conductive and thermally conductive slurry, stir and disperse for 60 minutes, adjust the viscosity to 3000-5000mPa·s to obtain electrode slurry. Coat the electrode slurry on the surface of the current collector, control the coating thickness to 150um, dry and roll to obtain a battery pole piece containing composite nano-silicon carbide.
[0025] Example 5: S1: Add 2.0 g of adhesive into 100 g of solvent and stir until completely dissolved to obtain adhesive glue; S2: Add 5.0 g of nano silicon carbide particles and 2.5 g of silicon carbide whiskers into 102 g of adhesive glue in proportion, stir and disperse at high speed for 30 minutes to form a thermal conductive glue; S3: Add 2.0 g of conductive agent to 109.5 g of thermal conductive adhesive and continue to disperse for 30 minutes to form a conductive thermal conductive slurry; S4: Add 88.5 g of active material to 111.5 g of conductive and thermally conductive slurry, stir and disperse for 60 minutes, adjust the viscosity to 3000-5000 mPa·s to obtain electrode slurry. Coat the electrode slurry on the surface of the current collector, control the coating thickness to 150 um, dry and roll to obtain a battery pole piece containing composite nano-silicon carbide.
[0026] Comparative Example 1: S1: Add 2.0 g of adhesive into 100 g of solvent and stir until completely dissolved to obtain adhesive glue.
[0027] S2: Add 2.0 g of nano silicon carbide particles into 102 g of the adhesive solution, stir and disperse at high speed for 30 minutes to form a thermal conductive adhesive solution.
[0028] S3: Add 2.0 g of the conductive agent into 104 g of the thermal conductive adhesive, and continue to stir and disperse at high speed for 30 minutes to form a conductive and thermal conductive slurry.
[0029] S4: Add 94.0g of active material to 106g of conductive and thermally conductive slurry, stir and disperse at high speed for 60 minutes, adjust the viscosity to 3000-5000mPa·s to obtain electrode slurry. Coat the electrode slurry on the surface of the current collector, control the coating thickness to 150um, dry and roll to obtain a battery pole piece containing composite nano-silicon carbide.
[0030] Comparative Example 2: S1: Add 2.0 g of adhesive into 100 g of solvent and stir until completely dissolved to obtain adhesive glue.
[0031] S2: Add 1.0 g of nano silicon carbide whiskers into 102 g of adhesive glue, stir and disperse at high speed for 30 minutes to form a thermal conductive glue.
[0032] S3: Add 2.0 g of conductive agent into 103 g of thermal conductive adhesive and continue to disperse for 30 minutes to form a conductive and thermally conductive slurry.
[0033] S4: Add 94.0g of active material to 105g of conductive and thermally conductive slurry, stir and disperse at high speed for 60 minutes, adjust the viscosity to 3000-5000mPa·s to obtain electrode slurry. Coat the electrode slurry on the surface of the current collector, control the coating thickness to 150um, dry and roll to obtain a battery pole piece containing composite nano-silicon carbide.
[0034] Comparative Example 3: S1: Add 2.0 g of adhesive into 100 g of solvent and stir until completely dissolved to obtain adhesive glue.
[0035] S2: Add 2.0 g of conductive agent into 102 g of thermal conductive adhesive and continue to disperse for 30 minutes to form a conductive and thermally conductive slurry.
[0036] S3: Add 96.0g of active material to 104g of conductive slurry, stir and disperse at high speed for 60 minutes, adjust the viscosity to 3000-5000mPa·s to obtain electrode slurry. Coat the electrode slurry on the surface of the current collector, control the coating thickness to 150um, dry and roll to obtain a battery pole piece containing composite nano-silicon carbide.
[0037] The battery performance tests of the above examples and comparative examples are shown in the following table: Table 1 Battery performance test table It can be seen from the data in Table 1 that the temperature rise of the pole piece batteries prepared in Example 1, Example 2 and Example 3 is relatively low at the 2C and 5C discharge rates. The data in Comparative Example 3 shows that the temperature rise of the pole piece battery without thermal conductive agent is relatively high; the data in Comparative Examples 2 and 3 show that the temperature rise of the battery is somewhat lower than that in Comparative Example 3 by adding only silicon carbide particles or silicon carbide whiskers, but the effect is not obvious. The data in Table 1 show that the heat dissipation capacity of sodium ion batteries can be effectively enhanced by the reasonable addition of silicon carbide particles and whiskers.
[0038] The present invention Figure 2 The large blue spherical substances are active material particles, the small black spherical substances are silicon carbide particles, and the long whiskers are silicon carbide whiskers.
[0039] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A sodium ion battery pole piece containing composite nano silicon carbide, characterized in that: The sodium ion battery pole piece includes the following components in proportion: 0.5Wt%~5Wt% nano silicon carbide particles; 0.5Wt%~5Wt% Silicon carbide whiskers; Wherein, the weight ratio of the nano silicon carbide particles to the silicon carbide whiskers is 1-2:
1.
2. A sodium ion battery pole piece containing composite nano-silicon carbide according to claim 1, characterized in that: The particle size of the nano silicon carbide particles is 50nm-500nm, the diameter of the silicon carbide whiskers is 0.2um-0.5um, and the length of the silicon carbide whiskers is 2um-10um.
3. A sodium ion battery pole piece containing composite nano-silicon carbide according to claim 1, characterized in that: Also includes ingredients in the following proportions: 0.5wt%~5wt% conductive agent; 1wt%~5wt% adhesive; 97.5wt%~80wt% active matter.
4. A method for preparing a sodium ion battery pole piece containing composite nano-silicon carbide, characterized in that: The following steps are involved: S1: Add 1-5 parts by weight of adhesive to 100 parts by weight of solvent and stir evenly to obtain adhesive solution; S2: adding 0.5-5.5 parts by weight of nano silicon carbide particles and 0.5-5.5 parts by weight of silicon carbide whiskers to the adhesive glue, wherein the nano silicon carbide particles and the silicon carbide whiskers are added to the adhesive glue in a weight ratio of 1-2:1 and dispersed evenly to form a thermal conductive glue; S3: adding 0.5-6 parts by weight of a conductive agent into 100 parts of a thermally conductive adhesive liquid and dispersing the conductive agent evenly to form a conductive and thermally conductive slurry; S4: adding 60-200 parts by weight of the active material into 100 parts of the conductive and thermal conductive slurry, and dispersing and homogenizing to obtain an electrode slurry; The electrode slurry is coated on the surface of the current collector with a coating thickness of 100 um to 300 um to obtain a battery electrode containing composite nano-silicon carbide.
5. The method for preparing a sodium ion battery pole piece containing composite nano-silicon carbide according to claim 4, characterized in that: The particle size of the active material is 5um~10um.
6. The method for preparing a sodium ion battery pole piece containing composite nano-silicon carbide according to claim 4, characterized in that: The coating thickness of the battery pole piece containing composite nano-silicon carbide is 100um~300um.
7. The method for preparing a sodium ion battery pole piece containing composite nano-silicon carbide according to claim 4, characterized in that: The solid content of the electrode slurry is 40wt%~65wt%, and the viscosity of the electrode slurry is 3000mPa·s~5000mPa·s.
Citation Information
Patent Citations
Carbonization base electrode material
CN103137973A
Silicon-carbon composite material for secondary lithium battery and preparation method thereof
CN113823772A
Preparation method of silicon carbide and carbon core-shell structure whisker and heat-conducting and wave-absorbing patch and corresponding products
CN116375034A
Preparation method of high-rate lithium ion battery negative electrode material
CN117476882A
Electrode active material-carbon nanotube composite and manufacturing method thereof
JP2017084759A
Cited By
Positive plate, sodium ion battery and application of sodium ion battery
CN120413616A
Positive electrode sheet, sodium-ion battery and application thereof
CN120413616B
Heat-conducting fire extinguishing film as well as preparation method and application thereof
CN120718312A